KAJIAN PRODUKTIVITAS ALAT MUAT KAYU KPH2 DI BKPH GUNUNG HALU, KPH BANDUNG SELATAN PERUM PERHUTANI UNIT III JAWA BARAT - Zakaria Basari; Sona Suhartana; Wesman Endom; Dulsalam Dulsalam; Yayan Sugilar (Pusat Penelitian dan Pengembangan Hasil Hutan, 2002)
The KPH2 a type of equipment for wood loading into truck was designed by Forest Engeenering and Forest Harvest Divition Forest Products Research Centre Bogor. An operation trial has been done in BKPH Gunung hatu, Bandung Selatan Forest District, Perum Perhutani Unit III West Java.The objective of this study is to see the productivity and operation cost of loading rasamala log ( Altingia excelsa) into truck. using a helper KPH2 and by manual system.The results showed that productivity of KPH2 equipment and manual were 0.02 m3 minute/m and 0,04 m/minute/m, with operation cost of Rp 18.523,00/m3 and Rp 2.000,00/m3 respectively.